CORROSION AND FATIGUE OF HEAT TREATED MARTENSITIC STAINLESS STEEL 1.4542 USED FOR GEOTHERMAL APPLICATIONS - Pfennig, Anja; Kranzmann, Axel (MATTER: International Journal of Science and Technology, 2019)
During capture and storage technology (CCS) as well as in geothermal energy production steels need to withstand the corrosive environment such as: heat, pressure, salinity of the aquifer and CO2-partial pressure. 1.4542 shows unusual corrosion phenomena, but is still sufficiently resistant in corrosive environments. To better understand its behaviour differently heat treated coupons of 1.4542 and for comparison X20Cr13 and X46Cr13 were kept in the artificial brine of the Northern German Basin at T=60 °C. Ambient pressure as well as p=100 bar for 700 h - 8000 h in water saturated supercritical CO2 and CO2-saturated synthetic aquifer environment was applied. Fatigue tests were performed via push-pull tests with a series of 30 specimens from 150 MPa to 500 MPa (sinusoidal dynamic test loads, R=-1; resonant frequency ~ 30 Hz). FeCO3 and FeOOH are corrosion products also after dynamic corrosion tests. Martensitic microstructure offers good corrosion resistance in geothermal environment. The S-N-curve showing no typical fatigue strength and very steep slopes of possible fatigue strength for finite life. Possible influencing artefacts, such as Al-inclusions could not be correlated to early rupture despite specimens containing inclusions at the fracture surface and cross section reached lower number of cycles. Applied potential proofed to enhance fatigue life tremendously.